Membrane separation process modeling for CO2 partial removal in prepurification of air separation units. Issue 12 (2nd December 2019) - Wu, Dongyun; Yi, Chunhai; Wang, Wei; Wang, Yixuan; Yang, Bolun; Qi, Suitao
Abstract: A novel membrane/adsorption hybrid system was proposed for air prepurification in large scale air separation units. Mathematical models were established for cocurrent and countercurrent flow patterns with crude nitrogen as purge stream to describe the membrane separation performance. The experimental and predicted results are in good agreement confirming the validity of the mathematical models. Effects of membrane properties and operation parameters on O2 recovery, N2 recovery, and membrane area requirement were investigated. For countercurrent flow pattern, O2 recovery and N2 recovery were larger than 98 and 99%, respectively, and membrane area requirement was less than 0.25 m 2 /m 3 h −1 with feed side pressure of 0.6 MPa and the purge gas/feed gas ratio of 0.2.